The Effectiveness of Nutrition Education on Changes in Household Consumption Behavior - Isnani Nurhayati; Herlina Lidiyawati (PT. Anagata Sembagi Education, 2026)
Family dietary consumption behavior that does not comply with balanced nutrition principles remains a major public health concern. Nutrition education is widely implemented as a promotive and preventive strategy; however, its effectiveness in producing actual behavioral change requires empirical validation. This study aimed to examine the effectiveness of nutrition education on changes in family consumption behavior compared to a control group. A quantitative quasi-experimental design with a pretest–posttest control group was employed. Families were assigned to intervention and control groups. The intervention group received structured nutrition education, while the control group received no or standard education. Dietary consumption behavior was measured using a structured questionnaire before and after the intervention. Data analysis included within- and between-group comparisons and ANCOVA to control for confounding variables. The results demonstrated a statistically significant improvement in consumption behavior scores in the intervention group compared to the control group. The difference remained significant after controlling for confounders. These findings indicate that nutrition education is effective in promoting meaningful changes in family dietary behavior beyond knowledge improvement alone. The study concludes that nutrition education constitutes an evidence-based intervention for improving family consumption behavior within public health programs.